Visualising the effect of freezing on the vascular system of wheat in three dimensions by in‐block imaging of dye‐infiltrated plants. (11th April 2022) - Livingston, David; Tuong, Tan; Tisdale, Ripley; Zobel, Rich
Abstract: Infrared thermography has shown after roots of grasses freeze, ice spreads into the crown and then acropetally into leaves initially through vascular bundles. Leaves freeze singly with the oldest leaves freezing first and the youngest freezing later. Visualising the vascular system in its native 3‐dimensional state will help in the understanding of this freezing process. A 2 cm section of the crown that had been infiltrated with aniline blue was embedded in paraffin and sectioned with a microtome. A photograph of the surface of the tissue in the paraffin block was taken after the microtome blade removed each 20 μm section. Two hundred to 300 images were imported into Adobe After Effects and a 3D volume of the region infiltrated by aniline blue dye was constructed. The reconstruction revealed that roots fed into what is functionally a region inside the crown that could act as a reservoir from which all the leaves are able to draw water. When a single root was fed dye solution, the entire region filled with dye and the vascular bundles of every leaf took up the dye; this indicated that the vascular system of roots was not paired with individual leaves. Fluorescence microscopy suggested the edge of the reservoir might be composed of phenolic compounds. When plants were frozen, the edges of the reservoir became leaky and dye solution spread into the mesophyll outside the reservoir. The significance of this change with regard to freezing tolerance is not known at this time. Thermal cameras that allow visualisation of water freezing in plants have shown that in crops like wheat, oats and barley, ice forms first at the bottom of the plant and then moves upwards into leaves through water conducting channels. Leaves freeze one at a time with the oldest leaves freezing first and then younger ones further up the stem freeze later. To better understand why plants freeze like this, we reconstructed a 3‐dimensional view of the water conducting channels. After placing the roots of a wheat plant in a blue dye and allowing it to pull the dye upwards into leaves, we took a part of the stem just above the roots and embedded it in paraffin. We used a microtome to slice a thin layer of the paraffin containing the plant and then photographed the surface after each layer was removed. After taking about 300 images, we used Adobe After Effects software to re‐construct the plant with the water conducting system in three dimensions. The 3D reconstruction showed that roots fed into a roughly spherical area at the bottom of the stem that could act as a kind of tank or reservoir from which the leaves pull up water. When we put just one root in dye, the entire reservoir filled up and the water conducting channels in every leaf took up the dye. This indicates that the water channels in roots were not directly connected to specific leaves as we had thought. When plants were frozen, the dye leaked out of the reservoir and spread into cells outside. Research is continuing to understand the significance of this change during freezing. It is possible that information about this effect can be used to help breeders develop more winter‐hardy crop plants.